Enhance Mahārah al-Kalām of 9th-Grade Students at MTs Haji Ilyas Using “Word Guessing Game” - Nor Holis bin Nafsah; Ahmad Royhan (INAIFAS PRESS, 2023)
The ability to speak Arabic needs to be supported by mastery of Arabic vocabulary, and one of the strategies is the application of the Arab word guessing method to students. The purpose of this study was to determine the improvement of Arabic language skills of 9th-Grade Students at MTs Haji Ilyas Jember students after the application of the word guessing method, in order to support the mastery of mahārah al-kalām students. This research uses qualitative methods with data collection techniques through pre-test, post-test, interview, observation and documentation. The results showed that the application of this method can improve students’ Arabic language skills. This is evidenced by 90% of students experiencing significant development after the implementation of this method, while the remaining 10% is considered sufficient. This shows that learning Arabic with the word guessing method can help students in mastering Arabic vocabulary as a support for mastery of mahārah al-kalām.